Central Sterile Services Department: psychosocial risks related to the prescribed organization of nursing work - Natascha Monteiro Medeiros; Daniela Silva dos Santos Schneider; Cecília Helena Glanzner (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: The aim of this study is to investigate the characteristics of work-flow organization of the Central Sterile Services Department and analyze whether nursing workers are subject to psychosocial risks. Method: Mixed study, carried out between November 2017 and July 2019 with nursing workers of the Department of Central Sterile Services of a university hospital. Sampling for the quantitative stage of this study consisted of 36 professionals who have filled the Prescribed Work Organization Scale form, followed by statistical analysis. Qualitative sampling was obtained through collective interview with 19 members of the nursing team. Results: Of the 36 nursing workers, 68.3% were female, 69.4% were over 45 years of age and 75% of the professionals assessed reported as being exposed to a medium psychosocial risk with the emergence of two categories. The aspects related to pleasure at work were highlighted as being the importance of the unit, indirect patient care, professional recognition, and teamwork. The main reported suffering triggers were the lack of human resources, supplies, maintenance, communication, and the devaluation of the unit. Conclusion: The prevalence of medium psychosocial risks indicated the need for actions aiming at improving work processes.